A CHARACTER EDUCATION MODEL BASED ON EPISTEMOLOGY REVELATION–REASON–SENSE: A STUDY OF IBN TAIMIYAH'S THOUGHTS - Samsuddin Samsuddin Samsuddin; Rahendra Maya; Abdul Jabar Idharudin; Mowafg Masuwd (STAI Sebelas April Sumedang, 2025)
This study stems from a concern over the moral and epistemological crisis that characterizes modern education, particularly in the post-truth era, where truth is often obscured by opinion and emotion. Current models of character education tend to be normative and pragmatic, lacking a solid epistemological foundation. To address this issue, the research explores the epistemology of wahyu–‘aql–ḥiss (revelation–reason–senses) in Ibn Taimiyah’s thought as the basis for developing an integrative and transcendental Islamic character education model. The study employs a qualitative-descriptive approach using library research and philosophical-hermeneutic analysis of Ibn Taimiyah’s seminal works—Dar’ Ta‘āruḍ al-‘Aql wa al-Naql, Majmū‘ al-Fatāwā, and al-Radd ‘ala al-Manṭiqiyyīn—supported by secondary literature from contemporary Islamic scholars. The results reveal that Ibn Taimiyah’s epistemology is structured upon three primary sources of knowledge: revelation as the absolute source of truth, reason as the means of rationalization, and the senses as empirical instruments for perceiving reality. These three dimensions form a harmonious and hierarchical system of knowledge under the supremacy of revelation. In the context of character education, this model emphasizes the balance between transcendental values, critical rationality, and empirical experience in shaping students’ moral character. The study concludes that the wahyu–‘aql–ḥiss epistemology is not merely theoretical but can serve as a pedagogical paradigm for designing Islamic character education grounded in divine values while remaining relevant to contemporary challenges. Further applied research is recommended to evaluate the practical effectiveness of this model across various educational levels.